Exploring the Use of WRF-ARW Model for Analyzing Heatwaves in Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
This study attempts to simulate heatwave events over Bangladesh using the WRF-ARW Model that could be used to implement a best practice strategy for predicting heatwaves in Bangladesh. In this research, 17 heatwave events were identified from the period between 2007 and 2022. The thresholds for heatwave events were considered when the maximum temperature from a weather station was above the 95th percentile for three consecutive days. After carefully identifying the events, all the events were simulated with the WRF-ARW model. Simulated temperature, relative humidity, and wind vector (direction and speed) were analyzed for this research. The synoptic conditions were synthesized for all the heatwave events. It was found that the propagation of warm temperatures corresponded to the movement of wind and was aptly supported by the presence of humidity in the region of interest. This information could be used at the operational level for predicting heatwaves.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(1), 2023, P 9-28